Current trends in extension training - Mishra, O.P.; Ganguli, D. (2002)
Extension Training has been perceived as a tool for Agricultural Human Resource Development (AHRD), which has received top priority by the World Bank and Indian Council of Agricultural Research (ICAR). Many developments have taken place in the field of Extension Training. This article focuses on the current trends in the use of extension training methods and new electronic technologies for giving training to the extension personnel. In past `Lecture method was most common way of training and AV aids like Chart, Posters, Black Board, etc. were used frequently. Now situation is going under drastic change and participative training methods like Case study, Simulation methods, Project method, Practical assignment, etc. are getting place in training to meet professional standards. Use of new electronic technologies viz., Computer, ICVT, Teleconferencing, Internet etc. in training are growing at faster rate. - Reproduced.
Keywords: Training